2007
DOI: 10.1016/j.jpainsymman.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for Women with Metastatic Breast Cancer: Results from a Pilot Study

Abstract: Metastatic breast cancer (MBC) remains a terminal illness for which major treatment advances are slow to appear, and hence it is crucial that effective palliative interventions be developed to reduce the cancer-related symptoms of women with this condition during the remaining years of their lives. This pilot/feasibility study examined a novel, yoga-based palliative intervention, the Yoga of Awareness Program, in a sample of women with MBC. The eight-week protocol included gentle yoga postures, breathing exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
146
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 53 publications
7
146
1
Order By: Relevance
“…36 The past decade of research has demonstrated a variety of therapeutic benefits associated with the practice of yoga in treating many illnesses, chronic diseases, and disabilities, such as chronic pain, 36 high blood pressure, 37 autism spectrum disorder, 38 trauma, 39 Alzheimer's disease, epilepsy, fibromyalgia, peripheral nervous system disorders, 10 fatigue and mood, 40,41 chronic insomnia, 42 depression, 43 heart attack and stroke, 36 and eating disorders, 44 as well as improved quality of life, 41 neuromuscular function, 45 flexibility, 46 and better physical, emotional, and spiritual wellness among patients with cancer. 47 For example, Carson and colleagues 47 looked at the effects of a novel yoga intervention-the Yoga Awareness Program-among 13 women with metastatic breast cancer. The 8-week yoga intervention included the practice of gentle yoga asanas, breathing exercises, meditation, didactic presentations, and group interchange.…”
Section: Therapeutic Yogamentioning
confidence: 99%
“…36 The past decade of research has demonstrated a variety of therapeutic benefits associated with the practice of yoga in treating many illnesses, chronic diseases, and disabilities, such as chronic pain, 36 high blood pressure, 37 autism spectrum disorder, 38 trauma, 39 Alzheimer's disease, epilepsy, fibromyalgia, peripheral nervous system disorders, 10 fatigue and mood, 40,41 chronic insomnia, 42 depression, 43 heart attack and stroke, 36 and eating disorders, 44 as well as improved quality of life, 41 neuromuscular function, 45 flexibility, 46 and better physical, emotional, and spiritual wellness among patients with cancer. 47 For example, Carson and colleagues 47 looked at the effects of a novel yoga intervention-the Yoga Awareness Program-among 13 women with metastatic breast cancer. The 8-week yoga intervention included the practice of gentle yoga asanas, breathing exercises, meditation, didactic presentations, and group interchange.…”
Section: Therapeutic Yogamentioning
confidence: 99%
“…11,13,16 Several studies have investigated the efficacy of a multimodality yoga intervention, which includes breathing, postures, and/or meditation, in a population of patients with cancer. [17][18][19][20][21][22][23][24][25][26][27][28][29] However, conclusive results are lacking. 30 Many studies have small and mixed samples (i.e., included both patients who were receiving cancer treatment and those post-treatment) and others have methodological limitations leading to challenges in drawing definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The latter two themes reflect physical and social perspectives -established topics in the cancer and yoga literature [14,15,22,36]. The complexities of how these women come to experience social and physical benefits and how these benefits are contextualised within the women's experiences of cancer treatment are explored.…”
Section: Discussionmentioning
confidence: 99%
“…Yoga has been identified as beneficial to psychological and physical well-being in a variety of healthy and non-healthy populations [4][5][6][7][8][9][10][11][12][13], including cancer [14][15][16][17][18][19][20][21][22][23][24]. Reported benefits of participating in yoga for cancer patients include reduction of treatment-induced side effects and relief of symptoms of the disease itself [14][15][16]: these are often measured on validated quantitative scales. Although randomised controlled trials (RCTs) are generally considered the gold standard for establishing causation in medical studies [25], qualitative research is also suggested to be beneficial as it explores patients' understanding and beliefs about an intervention, their expectations of possible outcomes, and their understanding of the impact, context and process of their participation [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation